Penyisipan Data Secara Reversible Pada Gambar Medis Menggunakan Metode Difference Expansion of Quad dan Fungsi Modulus - Arham, Aulia (UIN Imam Bonjol Padang, 2024)
The rapid advancement of the Internet of Things (IoT) brings convenience across various domains, but raises its own challenges, particularly concerning data security and privacy. Cryptography and steganography are two techniques used to secure data. Cryptography protects information by encrypting messages, while steganography hides the existence of data in other media. The embedding of data into other media like medical images necessitates specialized approaches to prevent potential distortion that may compromise their integrity. Distortion in medical images could lead to erroneous diagnoses. In this study, we introduce a reversible data embedding technique capable of returning storage media to its original state without distortion, utilizing the Difference Expansion of Quad and Modulus Function. This approach employs 2×2 pixel blocks to embed 3-bits of data. Our experiments on six medical images demonstrate that the proposed method offers substantial embedding capacity while maintaining high visual quality. The embedding capacity can reach 0.4834 bits per pixel (bpp) with a PSNR of 49.4330 dB. Experimental findings indicate that the proposed method outperforms previous techniques.